Ramifications of Artificial Intelligence on Organizational Performance in Nigeria - Godspower Onyekachukwu Ekwueme; Uchendu Onwusoronye Onwurah; Ifenyinwa Faith Ogbodo (Journal Majelis Paspama, 2024)
Artificial intelligence (AI) has been identified to be very significant in the twenty-first century in almost every discipline, including engineering, science, education, medical, business, accounting, finance, marketing, economics, manufacturing, the stock market, and law. This study examined the impact of artificial intelligence on organizational performance in a microfinance bank. Relevant data were drawn from selected one hundred (100) staff of XYZ Microfinance bank based in Nigeria, using a well-structured questionnaire. The data collected were descriptively analyzed. The results showed that artificial intelligence has positive impact on the organizational performance. The results also revealed that high cost of implementation, anxiety among workers, role displacement, ethical issues, significant investment in technology and training, among others are the challenges affecting the adoption of artificial intelligence in the business organization in Nigeria. The study recommends that Businesses must take proactive measures to address the obstacles to AI adoption if they want to optimize the technology's beneficial effects on organizational performance.